2023
DOI: 10.1002/ange.202213511
|View full text |Cite
|
Sign up to set email alerts
|

Programming Photodegradability into Vinylic Polymers via Radical Ring‐Opening Polymerization

Abstract: Incorporation of photolabile moieties into the polymer backbone holds promise to remotely-control polymer degradation. However, suitable synthetic avenues are limited, especially for radical polymerizations. Here we report a strategy to program photodegradability into vinylic polymers by exploiting the wavelength selectivity of photocycloadditions for radical ring-opening polymerization (rROP). Irradiation of coumarin terminated allylic sulfides with UVA light initiated intramolecular [2+2] photocycloaddition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Meanwhile, a new resonance p1 of the resulting vinylarene proton d = 7.70 ppm arises in copolymer P1, conrming the ring-opening polymerization of the cyclic monomer. 18,36 The incorporation ratio of the styrylpyrene monomer and DMA determined from the integral of resonances p 1 and the methyl proton of DMA was 1.8%, slightly lower than the feed ratio. Monitoring the copolymerisation of SC5 and DMA revealed that while the conversion of both monomers increased with polymerisation time, the conversion of SC5 remains slightly below DMA over the entire polymerisation time (Fig.…”
Section: Development and Polymerization Of A Complementary Photoreact...mentioning
confidence: 95%
See 2 more Smart Citations
“…Meanwhile, a new resonance p1 of the resulting vinylarene proton d = 7.70 ppm arises in copolymer P1, conrming the ring-opening polymerization of the cyclic monomer. 18,36 The incorporation ratio of the styrylpyrene monomer and DMA determined from the integral of resonances p 1 and the methyl proton of DMA was 1.8%, slightly lower than the feed ratio. Monitoring the copolymerisation of SC5 and DMA revealed that while the conversion of both monomers increased with polymerisation time, the conversion of SC5 remains slightly below DMA over the entire polymerisation time (Fig.…”
Section: Development and Polymerization Of A Complementary Photoreact...mentioning
confidence: 95%
“…As SC5 is the only monomer within P3 that absorbs light at l = 360 nm (as shown in Fig. 1B), 36,52 the SEC-UV trace of P3 at l = 360 nm was used to investigate the origin of the shoulder of P3. The SEC-UV trace of P3 thus only represents the chain-extension product, i.e.…”
Section: Photo-depolymerization As a Function Of Wavelengthmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, Do et al demonstrated a polymer ligation system where UVA light was used to polymerise a multicomponent polymer and shorter wavelength UVB light was later applied for degradation. [25] Action plots are perhaps even more critical where two colors of light are required to facilitate a photochemical reaction, such as in emerging 3D printing technologies. Here, they are essential to determine the specific wavelengths where individual chromophores, or synthetic steps, can be addressed individually for synergistic, orthogonal, antagonistic or sequential purposes.…”
Section: Implications For Applicationsmentioning
confidence: 99%
“…To this end, Do et al demonstrated a polymer ligation system where UVA light was used to polymerise a multicomponent polymer and shorter wavelength UVB light was later applied for degradation. [ 25 ]…”
Section: Implications For Applicationsmentioning
confidence: 99%